A new species of Bernardia (Euphorbiaceae, Acalyphoideae) with stellate trichomes from South America - Carrión, Juan F.; Amorim, André M. (Phytotaxa, 2024)
Bernardia fluviatilis is described as a new species of Euphorbiaceae from the Upper Paraguay River Basin in central South America. A literature review, examination of herbarium specimens, and fieldwork suggest that the new taxon is most similar to B. argentinensis but differs by its young branches covered by a sparsely sericeous indumentum of simple trichomes, usually shorter staminate peduncles, cymules scattered along the axis of the staminate inflorescence, and staminate flower pedicel usually glabrous. Illustrations, photographs, information about the distribution, habitat, and conservation status of the new species, and a key to the morphologically similar species, are also provided.